1970
DOI: 10.3329/fmcj.v6i1.7406
|View full text |Cite
|
Sign up to set email alerts
|

Comments on Evaluation of Endoscopic Findings and Detection of <i>H. pylori</i> Antibody by Serum IgG ELISA

Abstract: Bangladesh is a developing country with high prevalence of peptic ulcer disease and H. pylori infection. During the period of January 2007 to December 2007, a cross sectional study was conducted. In this study, serum samples were collected from 86 dyspeptic patients undergoing upper GIT endoscopy to determine anti-H. pylori IgG antibody by serum ELISA and was evaluated with endoscopic findings. Out of 86 study patients, gastro-duodenal mucosa was found normal in 58.14%, gastritis in 11.63%, duodenitis 2.33%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Among findings 12.7% had PUD, 3% gastric ulcer, 7% gastritis, 5.3% gastric tumor, 14.7% oesophageal varices, 5% reflux oesophagitis, 2.3% oesophageal carcinoma and 3% others (Table-V). This study finding is more or less similar with other findings revealed by endoscopy in Bangladesh 16 where gastroduodenal mucosa was found normal in 58.14%, gastritis in 11.63%, duodenitis 2.33%, reflux oesophagitis 4.65%, peptic ulcer 17.44% and carcinoma of stomach 5.81%. In another study in Bangladesh, endoscopy revealed that duodenal ulcer 34% was the most common cause of UGI bleeding followed by rupture of portal varices 16%, neoplasm 10%, gastric ulcer 08% and gastric erosion 06% 8 .…”
Section: Resultssupporting
confidence: 90%
“…Among findings 12.7% had PUD, 3% gastric ulcer, 7% gastritis, 5.3% gastric tumor, 14.7% oesophageal varices, 5% reflux oesophagitis, 2.3% oesophageal carcinoma and 3% others (Table-V). This study finding is more or less similar with other findings revealed by endoscopy in Bangladesh 16 where gastroduodenal mucosa was found normal in 58.14%, gastritis in 11.63%, duodenitis 2.33%, reflux oesophagitis 4.65%, peptic ulcer 17.44% and carcinoma of stomach 5.81%. In another study in Bangladesh, endoscopy revealed that duodenal ulcer 34% was the most common cause of UGI bleeding followed by rupture of portal varices 16%, neoplasm 10%, gastric ulcer 08% and gastric erosion 06% 8 .…”
Section: Resultssupporting
confidence: 90%
“…Patients presented with the symptoms of dyspepsia for more than 1 month were included in this study. 27 Individuals having severe medical or surgical illness such as asthma, COPD, previous gastric surgery etc and history of intake of proton pump inhibitors, non-steroidal anti-inflammatory drugs, colloidal bismuth compounds, or antibiotics for eradication of H. Pylori over the past four weeks of enrolment were excluded from this study. 28 After taking written informed consent from each patient, four endoscopic gastric biopsy tissue were collected from lesion and surrounding sites in gastric antrum and body.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“… 5 Individuals already receiving triple therapy for H. pylori eradication, therapy in the previous 2 months, had taken anti-ulcerant drugs including proton pump inhibitors (PPI), painkillers such as nonsteroidal anti-inflammatory drugs (NSAID), or any antibiotic 1 month before enrollment were ultimately excluded from this study. 7 - 9 …”
Section: Methodsmentioning
confidence: 99%